Experiences with CBP from Uganda - Blomley, Tom; Mukasa, Paul Kasule; Nunan, Fiona; Kiberu, Charles (My University, 2004)
The Government of Uganda is strongly committed to decentralisation, as evidenced by the devolution of responsibilities for local planning, resource allocation and budgeting, and investment management to local governments. It is a statutory requirement for each local government to produce a three-year integrated rolling development plan. The Local Government Act 1997 created five tiers of Local Councils (see Table 1). The highest level is the District/City Council (lower council level five, or LC5). This is followed by the county/municipal council (LC4); the sub-county/municipal division/town council (LC3); the parish/ward council (LC2); and the village council (LC1). The table below summarises the nature of local council structures, their populations, and roles. Prior to the introduction of the Community-based Planning project in Uganda, there were a number of participatory planning models in use, ranging from the use of Participatory Rural Appraisal (PRA) techniques for identifying community needs, to the involvement of communities in the provision of services and maintenance thereafter. Uganda has had an innovative Local Government Development Programme (LGDP) that has made great strides in the development of local government and lower level structures. However the Ministry recognised that it did not sufficiently address the strengthening of the lowest levels (LC2 and LC1) and so was keen to be a partner in the four-country project, and see how CBP could complement what Uganda was already undertaking. A steering group was formed to oversee the implementation of the CBP project, which consisted of the Office of the Prime Minister, the Local Government Development Programme, Plan for Modernisation of Agriculture (PMA), CARE International, Bushenyi District Local Government1, United Nations Capital Development Fund (UNCDF), and Uganda Participatory Development Network (UPDNet).